Electroconvulsive Therapy in the Management of Schizophrenia: A Systematic Review in Emergency Nursing Practice - Deeksha Pandey; Divyanshu Dhami (International Journal of Emergency and Trauma Nursing and Practices, 2025)
Electroconvulsive therapy (ECT) is a well-established treatment for various psychiatric disorders, including schizophrenia, particularly in cases where patients are resistant to conventional treatments. Schizophrenia, a chronic and severe psychiatric disorder, often presents with a combination of positive symptoms (such as hallucinations and delusions), negative symptoms (such as social withdrawal and emotional blunting), and cognitive impairments. While antipsychotic medications are the primary treatment, approximately 20–30% of individuals with schizophrenia do not respond adequately to these drugs, a condition known as treatment-resistant schizophrenia (TRS). For these patients, ECT has emerged as a crucial adjunctive therapy. This systematic review analyzes randomized controlled trials (RCTs) and observational studies to assess the efficacy, safety, and clinical applicability of electroconvulsive therapy (ECT) in the treatment of schizophrenia, with a particular focus on treatment-resistant cases. The review evaluates the impact of ECT on positive, negative, and cognitive symptoms, key components of schizophrenia symptomatology. Findings indicate that ECT is particularly effective in reducing positive symptoms, providing rapid relief from hallucinations and delusions. In addition, ECT has a moderate effect on negative symptoms, contributing to improvements in emotional engagement and social interaction when combined with ongoing pharmacological treatments. While ECT has shown substantial therapeutic benefits, it is not without risks. Cognitive side effects, particularly short-term memory loss, remain a primary concern. However, recent advancements in ECT technique, such as the use of anesthesia and refined electrode placement, have reduced the incidence of these adverse effects, making ECT a safer option than in the past. This review emphasizes the importance of ECT as an adjunctive treatment in cases of treatment-resistant schizophrenia, while also highlighting the need for further research to optimize treatment protocols and minimize cognitive side effects.
Keywords: Electroconvulsive therapy; Schizophrenia; cognitive side effects; psychosis; systematic review; treatment-resistant